THE INFLUENCE OF COMPENSATION AND MOTIVATION ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT PT SELAMAT SUKSES ABADI, MEDAN CITY - Berwinto, Berwinto; Silalahi, Marto; Sherly, Sherly; Butarbutar, Marisi; Efendi, Efendi (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2025)
The study aims to describe compensation, motivation, employee performance, and job satisfaction at PT Selamat Sukses Abadi Medan City. It also seeks to understand how compensation and motivation affect job satisfaction, both together and separately, as well as the impact of job satisfaction on employee performance. The research involved 66 permanent employees and utilized qualitative and quantitative data from questionnaires, interviews, and documentation. The findings showed that all factors—compensation, motivation, job satisfaction, and employee performance—were positively viewed by participants. Compensation and motivation significantly influenced job satisfaction, which in turn positively affected employee performance. A strong correlation was found between these factors. The study suggests the company should enhance compensation through better employee benefits, foster motivation through supervision and encouragement, conduct employee assessments for promotions, and offer training to improve employee skills, leading to better performance and job satisfaction. Keywords: Compensation, Motivation, Employee Performance, Job Satisfaction